“Purpose” and “Domain”: Two Concepts Translated as “Sonzai-igi,” and Their Relationship to “Keiei-rinen” - Haruhiko NOBAYASHI (AAOS Transactions)
The terms “purpose” and “domain” are both translated as “Sonzai-igi.” Furthermore, “purpose” is also said to be included within “Keiei-rinen.” Based on previous research, this study documents the relationship between “Keiei-rinen,” “purpose,” and “domain,” and presents related discussion. “Purpose” shows the social nature of a company （enterprise）, while “domain” indicates the strategic nature. This study clarified that both “purpose” and “domain” are component elements of “Keiei-rinen,” and that “purpose” often has the meaning （significance） of “domain.” By examining the structure of “Keiei-rinen,” we established that “purpose” is often placed at the apex, and is something that emphasizes the social nature of a company （i.e., corporate sociality）. Additionally, inasmuch as “purpose” frequently has the meaning of “domain,” by placing it at the topmost position, a company’s strategic nature （strategic approach, strategic thinking, etc.） is also emphasized.